The regulation and mechanism of the cAMP-PKA pathway on PTSD-like behaviors exacerbated by alcohol exposure - Zhao, Shuang; Zhao, Wei; Wang, Ziqi; Chen, Xiaofei; Zong, Fangjiao; Zhang, Hanting (Frontiers in Pharmacology, 2025)
Background Alcohol use disorder (AUD) and post-traumatic stress disorder (PTSD) exhibit a significant degree of comorbidity. Nevertheless, the specific effects and underlying mechanisms by which alcohol, as a risk factor, contributes to the development of PTSD-ike phenotypes remain poorly understood. Both chronic alcohol consumption and exposure to traumatic stress can lead to synaptic damage in the hippocampus, potentially serving as a neurobiological basis for the exacerbation of PTSD induced by alcohol.MethodsIn this study, an animal model was established by allowing mice to voluntarily consume alcohol for 2 weeks, followed by exposure to a single prolonged stress combined with foot shock (SPS&FS). Subsequently, the mice received an intraperitoneal injection of rolipram (1 mg/kg), and behavioral, biochemical, and morphological analyses were performed.ResultsThe findings revealed that individuals with early alcohol exposure exhibited more pronounced deficits in fear extinction during the fear extinction task (FET) and displayed higher levels of anxiety-like behavior in both the open field test (OFT) and the elevated plus maze test (EPM). Activation of cAMP-PKA signaling enhanced the downregulation of brain-derived neurotrophic factor (BDNF) and tyrosine kinase receptor B (TrkB), upregulated the expression of PSD95, synaptophysin, AMPA, and NMDA receptor subtypes, and reversed the impairment of CA1 synaptic function and dendritic structure in the hippocampus.ConclusionActivation of the cAMP-PKA pathway facilitated fear extinction in PTSD mice with early alcohol exposure, alleviated anxiety-like behavior, attenuated symptoms of AUD following ethanol relapses. These findings suggest that modulating hippocampal synaptic plasticity by activating the cAMP-PKA pathway may represent a promising therapeutic approach for attenuating alcohol-exacerbated PTSD-like behaviors.